2006
DOI: 10.1007/s11422-006-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

“They probably aren’t named Rachel”: Young children’s scientist identities as emergent multimodal narratives

Abstract: In this research we put forth a theoretical framework that explores the nature and value of multi-modal narratives as a tool for studying young children's conceptions of themselves as scientists as they exist in relation to scientists out in the world. This framework shapes and is shaped by an empirical study that took place within the context of a year-long program that engaged children in integrated science-literacy experiences around two unitsone on matter and one on a forest ecosystem. Thirty-six children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Maria Varelas' and Justine Kane's research with students of color (Black and Latino/a) has shown how academic and disciplinary identities become intricately fused as students try to make sense of the disciplinary practices of science in which they engage and of the institutional norms of schools and schooling that they experience [Kane, 2009[Kane, , 2012aTucker-Raymond, Varelas, & Pappas, 2007TuckerRaymond, Varelas, Pappas, & Keblawe-Shamah, 2012;Varelas, Kane, & Wylie, 2011. In one study, Varelas and Kane [Varelas et al, 2011] uncovered how young primary-grade Black children, in almost exclusively Black schools and in classrooms where their teachers attempted to engage them in meaningful scientific practices, were constructing academic and science identities that included conflicting practices, behaviors, ideologies, and habits of mind.…”
Section: Academic Identity and Its Influence On Disciplinary Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Maria Varelas' and Justine Kane's research with students of color (Black and Latino/a) has shown how academic and disciplinary identities become intricately fused as students try to make sense of the disciplinary practices of science in which they engage and of the institutional norms of schools and schooling that they experience [Kane, 2009[Kane, , 2012aTucker-Raymond, Varelas, & Pappas, 2007TuckerRaymond, Varelas, Pappas, & Keblawe-Shamah, 2012;Varelas, Kane, & Wylie, 2011. In one study, Varelas and Kane [Varelas et al, 2011] uncovered how young primary-grade Black children, in almost exclusively Black schools and in classrooms where their teachers attempted to engage them in meaningful scientific practices, were constructing academic and science identities that included conflicting practices, behaviors, ideologies, and habits of mind.…”
Section: Academic Identity and Its Influence On Disciplinary Identitymentioning
confidence: 99%
“…In addition, Varelas with Eli Tucker-Raymond and other colleagues have examined in a series of studies [Tucker-Raymond, Varelas, & Pappas, 2007TuckerRaymond et al, 2012] how young mostly Latino/a and African American children across first to third grades drew and talked about instances when they were scientists. The studies used a pre-mid-post design to explore changes relative to the children's positioning vis-à-vis the practice of science as they spent a year in their classrooms exploring science in extended units engaging with texts, hands-on explorations, writing, drawing, acting out, muraling, and talking science.…”
Section: Identity Construction Interwoven With Knowledge Constructionmentioning
confidence: 99%
“…This should not, however, suggest that identities are exclusively enduring, unified essences or core‐selves isolated from social interactions. Self‐understandings change over time, and they have an historical component in that they are “ accumulations of daily stories and positionings” (Tucker‐Raymond, Varelas, Pappas, Korzh, & Wentland, 2007, p. 561, italics in original). Interestingly, people tend to label and, thereby, “fix” their identities by using language that suggests permanence in relation to “an identity.” Sfard and Prusak (2005) refer to this as the “overpowering proclivity for ‘ is ‐sentences”’ (p. 16, italics in original).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Por esse motivo, nos artigos mais recentes que usaram o DAST, os pesquisadores incorporaram também uma etapa de entrevista, na qual as crianças podem expressar suas ideias e contar a história inspiradora dos seus desenhos (p. ex., Miller, 1993;Tucker-Raymond, Varelas, Pappas, Korzh, & Wentland, 2007).…”
Section: Quais As Principais Estratégias Usadas Para Acessar As Conceunclassified